Gluten-free instant noodles based on mocaf flour - Ariani Dini; Rahayu Novita Herawati Ervika; Nurhayati Rifa; Angwar Mukhamad (BIO Web of Conferences)
Background: Noodles are commonly made from wheat flour, which is an imported commodity. New innovation is needed by developing local food ingredients to make noodles. Mocaf exhibits properties such as viscosity, gelatinization, dehydration power, and solubility similar to wheat flour, so it can be used as a substitute ingredient in the developing of food products based on wheat flour. This study aims to develop gluten-free instant noodles using mocaf (modified cassava flour). Methods: The experimental design used a completely randomized design with five variations of rice flour and sago flour. Five noodle formulas were tested for their physical and sensory properties. The most favorable formula was analyzed for its nutritional content. Each treatment was set in duplicates, while analyses were performed in three replicates. All statistical analyses were performed with SPSS 23. Results: The most favorable formula was Mo4, which contains 6.15% water, 2.65% ash, 14.7% fat, 74.60% carbohydrate, 526 kcal total energy, 0.95% total sugar, 0.06% trans fat, and 4.12% dietary fiber. Conclusions: The preferred noodle contains 4.12% of dietary fiber, thus qualifying as a good source of dietary fiber. This noodle can become an alternative healthy food for individuals with gluten intolerance.